SAMARKAND’S TOPONYMY: A WINDOW INTO THE CITY’S HISTORICAL AND CULTURAL LEGACY - Tursunov Javlonbek Akrom o‘g‘li (Western European Studies, 2024)
Samarkand, a city with over two millennia of history, serves as a crossroads of civilizations and a testament to cultural, linguistic, and historical interweaving. This article delves into the toponymic heritage of Samarkand, tracing the evolution of its place names from ancient times to the present. It examines the significance of these names in understanding the city’s socio-political and cultural transformations. Additionally, the paper highlights the extensive preservation efforts undertaken since Uzbekistan's independence, which have restored Samarkand’s monuments and historical sites to their former glory. The study underscores the importance of collaborative research in exploring the etymology and historical context of Samarkand’s toponyms to preserve this invaluable heritage for future generations
Keywords: Samarkand; toponymy; Samarkand’s history; etymology